Edukasi Literasi Keuangan Untuk Anak Usia Dini Hingga Remaja - Sabila, Rizky Putri; Pratiwi, Zahra Yuni; Stella, Stella; Aminah, Nur; Putra, Getrudis Pratama; Sompie, DM. Christyana Michelle Ayu; Pramudia, Anatasya Silvi; Pasha, Rere Shakila; Amanda, Ocha Dhea; Lim, Razel; Fifiyanti, Nur; Valesca, Jesslyn; Fadhilah, Khalishah Salwa; Nugroho, Shabrina Salma; Simon, Anderson; Meylani, Herti (Universitas Pahlawan Tuanku Tambusai, 2024)
Financial literacy education at an early age to teenagers is an increasingly important topic in efforts to increase the younger generation's understanding of financial management. This article explores the importance of financial literacy education from an early age as a foundation for sustainable learning. This approach not only prepares children and teens to manage their money wisely, but also develops the skills necessary to make smart financial decisions in the future. Through a comparison of different teaching methods and an emphasis on collaboration between schools, families, and communities, this article identifies effective strategies for improving the financial literacy of the next generation. By providing strong knowledge about financial management from an early age, we can prepare the younger generation to face future financial challenges with more confidence and competence.